ESR dating applied to optically bleached quartz - A comparison with 40Ar/39Ar chronologies on Italian Middle Pleistocene sequences. (10th August 2020) - Voinchet, P.; Pereira, A.; Nomade, S.; Falguères, C.; Biddittu, I.; Piperno, M.; Moncel, M.-H.; Bahain, J.-J.
Abstract: The geological sequences of numerous Lower and Middle Palaeolithic sites of central and southern Italy, found in fluvio-lacustrine contexts and rich both in archaeological and palaeontological remains, have recorded various volcanic events all along the Middle Pleistocene timescale. These sedimentary sequences made of detritic and volcanic materials are suitable to compare independent numerical geochronological methods and thus develop a multi-method approach relying especially ESR method applied to optically bleached fluvial quartz and the 40 Ar/ 39 Ar on single grain isotopic method applied to potassium feldspars. In this present paper, geochronological data obtained using these two methods were used on several Middle Pleistocene Italian sites including volcanic and fluvial but also archaeological levels: Isoletta and Lademagne in Lazio and Notarchirico in Basilicata. In this contribution, ESR age estimates were performed using a multi-centre approach from Al, Ti–Li and Ti–H centres. We demonstrate for these sites that ESR-based framework is overall consistent with the 40 Ar/ 39 Ar chronology that over the 700 and 350 ka time window. This comparison validates the multi-centre approach proposed and demonstrates that the use of Ti–H for samples with equivalent doses higher than 280–300 Gy leads to systematic age underestimates.